Evaluating the food safety and risk assessment evidence-base of polyethylene terephthalate oligomers: A systematic evidence map - Schreier, Verena N.; Çörek, Emre; Appenzeller-Herzog, Christian; Brüschweiler, Beat J.; Geueke, Birgit; Wilks, Martin F.; Schilter, Benoit; Muncke, Jane; Simat, Thomas J.; Smieško, Martin; Roth, Nicolas; Odermatt, Alex (Environment international, 2023)
The presence of polyethylene terephthalate (PET) oligomers in food contact materials (FCMs) is well-documented. Consumers are exposed through their migration into foods and beverages; however, there is no specific guidance for their safety evaluation. This systematic evidence map (SEM) aims to identify and organize existing knowledge and associated gaps in hazard and exposure information on 34 PET oligomers to support regulatory decision-making. The methodology for this SEM was recently registered. A systematic search in bibliographic and gray literature sources was conducted and studies evaluated for inclusion according to the Populations, Exposures, Comparators, Outcomes, and Study type (PECOS) framework. Inclusion criteria were designed to record hazard and exposure information for all 34 PET oligomers and coded into the following evidence streams: human, animal, organism (non-animal), ex vivo, in vitro, in silico, migration, hydrolysis, and absorption, distribution, metabolism, excretion/toxicokinetics/pharmacokinetics (ADME/TK/PK) studies. Relevant information was extracted from eligible studies and synthesized according to the protocol. Literature searches yielded 7445 unique records, of which 96 were included. Data comprised migration (560 entries), ADME/TK/PK-related (253 entries), health/bioactivity (98 entries) and very few hydrolysis studies (7 entries). Cyclic oligomers were studied more frequently than linear PET oligomers. In vitro results indicated that hydrolysis of cyclic oligomers generated a mixture of linear oligomers, but not monomers, potentially allowing their absorption in the gastrointestinal tract. Cyclic dimers, linear trimers and the respective smaller oligomers exhibit physico-chemical properties making oral absorption more likely. Information on health/bioactivity effects of oligomers was almost non-existent, except for limited data on mutagenicity. This SEM revealed substantial deficiencies in the available evidence on ADME/TK/PK, hydrolysis, and health/bioactivity effects of PET oligomers, currently preventing appropriate risk assessment. It is essential to develop more systematic and tiered approaches to address the identified research needs and assess the risks of PET oligomers.